2021
DOI: 10.1051/e3sconf/202130603004
|View full text |Cite
|
Sign up to set email alerts
|

Development of self-sufficiency village for seed provision of superior variety in Majalengka Regency

Abstract: Farmer group-based seed production can support the provision of quality seed in areas according to consumer preferences. The purpose of the study was to determine the role of the Seed Self-sufficiency Village (SSV) in providing and accelerating the adoption of new high-yielding varieties of rice. This study used primary data from the assistance of the SSV Field School Model, which was carried out in the Gangsa I Farmers Group, Jatitengah Village, Jatitujuh Subdistrict, Majalengka Regency, West Java. Data on se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Previous research stated that the study of consumer preferences was very important in supporting the successful introduction of MVs, which includes study not only of climatic factors, regional ecology, variety attributes, but also farmer gender [21]. The results from another research also revealed that the existence of MVs that match consumer preferences can support the sustainability of the VSPGs in producing seeds [22].…”
Section: A Nationwide Seed Production Network For In-situ Seed Provisionmentioning
confidence: 99%
“…Previous research stated that the study of consumer preferences was very important in supporting the successful introduction of MVs, which includes study not only of climatic factors, regional ecology, variety attributes, but also farmer gender [21]. The results from another research also revealed that the existence of MVs that match consumer preferences can support the sustainability of the VSPGs in producing seeds [22].…”
Section: A Nationwide Seed Production Network For In-situ Seed Provisionmentioning
confidence: 99%